EMFi-Based Ultrasonic Sensory Array for 3D Localization of Reflectors Using Positioning Algorithms - Jimenez Martin, Ana; Hernandez Alonso, Alvaro; Ruiz, Daniel; Gude, Isaac; De Marziani, Carlos; Perez, Maria Carmen; Alvarez, Fernando J.; Gutierrez, Cesar; Urena, Jesus (IEEE sensors journal, 2015)
This paper describes a first prototype of an airborne ultrasonic array that combines pulse-compression techniques with positioning algorithms in order to achieve accurate determination of the position of the reflectors placed in front of the array. The new sensory system is based on an array with four independently controlled emitters and a receiver. The emitters are made of ferroelectrets as active material, leveraging their features to produce broadband air-coupled ultrasonic transducers at low cost. The ultrasonic emissions are encoded with an orthogonal Kasami sequence for each transducer, making possible to transmit simultaneously from each one. Furthermore, one of the main novelties of the proposal is that reflectors are located by means of a spherical trilateration algorithm that uses the time-of-flight of the ultrasonic signals from each transmitter to the receiver, bounced back by the reflector.